Four new species in subsection Asterotricha for the genus Onosma L. (Boraginaceae) from flora of Iran. Issue 3 (3rd September 2020) - Attar, Farideh; Sotoodeh, Arash; Mirtadzadini, Mansour
Abstract : Onosma khorramabadensis, O. lorestanica, O. sahandica and O. kerendica are described and photographed as new species from Lorestan, Eest Azarbayejan and Kermanshah provinces of Iran. Based on Flora Iranica, all the new species can be placed in the sect. Onosma subsect. Asterotricha considering their stellate‐hairy tubercles on leaves. The first new species has some similarities to Onosma bilabiata and O. elwendica based on having accrescent and two connected calyx lobes, but can be distinguished by its stem leaves shape and size, elongate inflorescence and more characters. O. lorestanica is close to O. elwendica by having spathulate leaves shape and nearly same fruiting calyx length; however it differs by its dense short capitate cyme in flowering time, tubercles density and rays arrangements on the tubercles. O. sahandica can be also close to O. bilabiata and O. elwendica for its fruiting calyx length and corolla color, but differs by having free calyx lobes and not accrescent at fruiting time. O. kerendica is related to O. cardiostegia by its habit and inflorescence shape, but can be distinguished by length of lowest bracts, its inflorescence size in fruiting time, pedicel length and filaments attachment place. The recent introduced species, Onosma zagrica (Dehshiri, 2018) should be classified into subsection Asterotricha instead of being in subsection Onosma according to its description and type specimen examination. Distribution map, micrographs of details of important characteristics and a diagnostic key are presented.